Exploring Teachers’ Beliefs and the Teaching Profession in Aceh - Sri Rahayu Jumiati Ningsih; Ika Apriani Fata (Studies in English Language and Education, 2015)
Formal teaching is an intentional activity that requires teachers to have beliefs and experiences. Teachers’ beliefs are defined by Johnson (1994) as something that is formed early in life as a result of a person’s education and experience. Strong beliefs about learning and teaching are well established by the time a student completes schooling. This study intends to find out the beliefs of teachers of English at junior and senior high schools in Aceh. The study surveyed three qualified teachers as participants (in which one is also a vice-principal of his school) and used 15 questions to ascertain their techniques, beliefs and career paths. The results show that teachers’ beliefs are related to the teaching methodologies that they use. According to the teachers’ beliefs, the teaching methodologies should be varied from time by time according to the situation and the curriculum. Besides, each participant has committed to a career in the teaching profession persistently despite facing many obstacles and challenges during teaching and learning. The participants dreamt of being teachers since they were children. The authors suggest other researchers might see applications of this research for studying the benefits and weaknesses of different teaching methodologies based on teachers’ beliefs.